2015
DOI: 10.1002/ajoc.201500332
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aerobic Oxidative Dicarbonylation of Indoles toward Solvatochromic Fluorescent Indole‐Substituted Quinoxalines

Abstract: Copper-catalyzed, aerobic, oxidative, C3-dicarbonylation of indoles has been realizedd irectly from a-hydroxyketones,w hich serve as an efficient dicarbonylative reagent under mild conditions. The method is widely compatibility with various functional groups, offering as traightforward means to produce differenth eterocyclesubstituted quinoxalines in excellent yields. These diverse fluorescent quinoxalines exhibited photophysical properties and solvatochromism in certain rules. Based on control experiments, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…An easy modification of moieties or their position in quinoxaline core allows tuning the photophysical properties of compounds and opens the broad opportunity to search out more perspective luminescent materials. Recently, 2,3‐disubstituted quinoxalines bearing indole group have been reported (Figure ). These fluorescent structures with high degree of conjugation have favorable photophysical properties and proved to be interesting for potential application as fluorescence‐based sensors …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…An easy modification of moieties or their position in quinoxaline core allows tuning the photophysical properties of compounds and opens the broad opportunity to search out more perspective luminescent materials. Recently, 2,3‐disubstituted quinoxalines bearing indole group have been reported (Figure ). These fluorescent structures with high degree of conjugation have favorable photophysical properties and proved to be interesting for potential application as fluorescence‐based sensors …”
Section: Figurementioning
confidence: 99%
“…Recently, 2,3‐disubstituted quinoxalines bearing indole group have been reported (Figure ). These fluorescent structures with high degree of conjugation have favorable photophysical properties and proved to be interesting for potential application as fluorescence‐based sensors …”
Section: Figurementioning
confidence: 99%
“…The same group also discovered a Pd/Cu-based catalytic system for the same couplings, in which the peroxide oxidant was no longer required. [86] To the same end of indole-attached dicarbonyl products, methyl ketones, [87] α-carbonyl aldehydes, [88] and α-carbonyl methanols [89] were intensively found to be effective coupling partners under aerobic conditions (Scheme 33).…”
Section: Indole Acylationmentioning
confidence: 99%
“…[ 11 ] One example is the copper‐catalyzed produced different heterocycle‐substituted quinoxalines, which have high potential for metal ion detection due to their fluorescence structures. [ 12 ] Since Czarnik first reported that rhodamine B derivatives went through a ring‐opening reaction induced by Cu 2+ that caused fluorescence enhancement, increasing numbers of researchers have focused on the use of rhodamine derivatives as probes to detect metal ions. [ 13,14 ] Rhodamine derivatives are excellent choices for Cu 2+ detection because spiroamide rings do not show any emission in UV–vis and fluorescence spectra.…”
Section: Introductionmentioning
confidence: 99%